Thursday

July 24, 2014

July 24, 2014

Posted by **Natasha** on Sunday, October 7, 2012 at 5:08pm.

3x-10y+z=5

-4x+9y-z=-6

-13y+z=2

- pre calculus -
**Reiny**, Sunday, October 7, 2012 at 7:53pmI would use substitution to start:

from the 3rd: z = 13y + 2

into the 1st:

3x - 10y + 13y + 2 = 5

3x + 3y = 3

x+y=1

into the 2nd:

-4x + 9y - 13y - 2 = -6

-4x - 4y = -4

x + y = 1

Ahhh,

x+y = 1 and x+y = 1 don't have a real solution.

So the system has no unique solution.

check my arithmetic

**Related Questions**

Math - Solve the system using any algebraic method. 2x - 2y + z = 3 5y - z = -31...

solution - 5y^2-13y+6 If you wish to factor, the factors are: (5y - 3)(y - 2) ...

MATH - Solve system of equations algebraically. 1. 3x-3y=24 and 2x+5y=-37 2. -9x...

calculus - When using the substitution method to solve a nonlinear system of ...

Pre-calculus-check answers - Write the slope-intercept form of the equation of ...

algebra - Solve the system of equations using the addition (elimination) method...

Pre-Calculus - I have to use the substitution method to solve the system of ...

Algebra - Solve using the elimination method.Show work.If the system has no ...

Math - How do i solve using the elimination method. If the system has no ...

algebra - Solve using the substitution method. Show your work. If the system has...